2021
DOI: 10.21037/tcr-21-375
|View full text |Cite
|
Sign up to set email alerts
|

Atypical meningioma: a retrospective analysis of six cases and literature review

Abstract: Background: Atypical meningiomas (AM) are WHO grade II tumors with high heterogeneity and invasiveness, which are unique in their clinical presentation, imaging, pathology, treatment, and prognosis. In 2016, the diagnosis of AM remodified by the classification of central nervous system tumors of World Health Organization (WHO). In order to further analyze the diagnosis and treatment characteristics of AM, the clinical diagnosis, surgery treatment and follow-up data of 6 patients with AM in our hospital from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…Meningiomas have a strong female predominance, which is also documented in this study, as well as in retrospective South African-based case reviews of 52 meningiomas by Fynn et al,38 cases by Vivier et al and 48 cases by…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Meningiomas have a strong female predominance, which is also documented in this study, as well as in retrospective South African-based case reviews of 52 meningiomas by Fynn et al,38 cases by Vivier et al and 48 cases by…”
supporting
confidence: 88%
“… 37 They most characteristically show facilitated diffusion with increased signal on the ADC map 37 ; this study case did not show significant diffusion facilitation or restriction. An isolated WHO Grade II atypical variant was encountered; these lesions classically show heterogenous T1-WI and T2-WI signal intensity, prominent enhancement, significant perilesional oedema and a poor plane of separation from adjacent brain tissue; 38 however, this study case did not demonstrate any of these suspicious features, but instead showed a circumscribed, homogenous, solid and well marginated lesion with only mild perilesional oedema. An isolated case of anaplastic meningioma was also present.…”
Section: Discussioncontrasting
confidence: 54%
“…AMs represent less than one fifth of all meningiomas [ 16 ], and this is the reason why in the literature there are many case presentations, or the analyzed series are not very large [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MRI scans and the 3D-printed model confirmed that the right optic nerve was segmentally embedded in the tumor. Moreover, for this patent, intraoperative frozen-section pathology revealed atypical meningioma, which shows high invasiveness and thus required total resection to promote prognosis [ 19 ]. Owing to all these factors, the affected optic nerve was intentionally removed, which resulted in the loss of eyesight.…”
Section: Discussionmentioning
confidence: 99%